The Epic and War Narrative Approach in Live Transmedia Series: An Analysis of the Dream SMP Case - Legerén Lago, Beatriz; Barahona Martínez, Jaime Fernando; Molares Cardoso, Julinda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This analysis explores epic and war elements in transmedia series, focused on Dream SMP, Minecraft server Survival MultiPlayer is positioned as a key space for collaborative narratives with massive audiences. From a theoretical framework, archetypes, triggers, plots and the hero's journey are studied, applied to Dream SMP through a methodological model. The results reveal a transmedia narrative that combines war conflicts, political alliances and personal journeys, enriched by real-time interaction between creators and audiences, redefining the epic narrative in new media as a unique cultural phenomenon.